ANALYSIS EFFECT OF SERVICE RECOVERY ON CUSTOMER LOYALTY WITH SATISFACTION AND WOM (WORD OF MOUTH) AS MEDIATION VARIABLES AT FOUR-STAR HOTELS IN BATAM CITY - Lily Purwianti; Lidya Siska Khoviati (Journal of Business Studies and Management Review, 2021)
The purpose of this study was to analyze the effect of service recovery variables consisting of distributive justice, procedural justice and interactional justice on customer loyalty with satisfaction and WOM as a mediating variable in star hotels in Batam city. The sample of this research is local tourists who have stayed at four-star hotels in Batam City. The results of the study indicate the importance of a service provider to find out what consumers want by paying attention to constructive criticism in order to improve services that were previously not adequate. If the customer feels that the service recovery provided is appropriate and satisfied with it, then the customer often returns with the status of a loyal visitor and recommends it to others.